Disabled-by-design: effects of inaccessible urban public spaces on users of mobility assistive devices - a systematic review - Kapsalis, Efthimis; Jaeger, Nils; Hale, Jonathan (Disability and rehabilitation: Assistive technology, 2024)
Despite the increase of users of Mobility Assistive Devices (MobAD), there has been a lack of accessibility in urban environments in many parts of the world. We present a systematic review of how the inaccessible design of public spaces affects quality-of-life - including aspects of health and safety, independence, and social participation - of MobAD users. We conducted a literature search in three databases (i.e., Scopus, Web of Science, and PubMed) and initially discovered 3980 publications. We analysed 48 peer-reviewed journal articles published in English from 2005 to 2021 and assessed their quality of evidence via the Mixed Methods Appraisal Tool. Findings indicated a substantial number of inaccessible elements for MobAD users in public spaces. Pathway characteristics, boarding ramps, entrance features, confined spaces, and service surfaces were deemed to be the least accessible elements. These barriers had multifaceted effects on MobAD users' quality of life with aspects of physical health, mobility, and use of public transport being most affected. Notwithstanding that the reviewed studies mostly ocused on wheelchair users residing in high-income countries, this review outlines the critical role of the design of the built environment as a factor of disablement for MobAD users. We conclude by highlighting a few recommendations for future research and practice, especially inclusive approaches and adaptive techniques to assist MobAD users with performing tasks in public spaces independently. Implications for Rehabilitation Users of Mobility Assistive Devices experience a lack of accessibility provisions in public open spaces and buildings internationally. Physical barriers in public spaces substantially diminish the health and safety, autonomy, and social participation of users of Mobility Assistive Devices. There is a definite need for the adoption of inclusive strategies and adaptive techniques in placemaking processes so that users of Mobility Assistive Devices can have equitable access to public spaces.